Stereoselective Synthesis of 3,4-Dihydrobenzofuro[3,2-b]pyridin-2(1H)-ones Enabled by Pd/Chiral Isothiourea Relay Catalysis - Sayed, Mostafa; Shi, Zhipeng; Fan, Tao; Shen, Hong-Cheng; Han, Zhi-Yong (Synthesis, 2024)
A highly enantioselective [4+2] cyclization of azadienes with ketene in situ generated from Pd-catalyzed carbonylation of benzyl bromides, is established through Pd/chiral isothiourea relay catalysis. The key in this transformation is the formation of a C1-ammonium enolate from the in situ generated ketene and a chiral isothiourea catalyst, which subsequently undergoes a formal [4+2] reaction, leading to 3,4-dihydrobenzofuro[3,2-b]pyridine derivatives in high yields and excellent levels of stereoselectivity.
Keywords: relay catalysis; C1-ammonium enolate; chiral isothiourea; azadiene; asymmetric catalysis